EARNING MANAGEMENT DAN RELEVANSI INFOMASI AKUNTANSI: PENDEKATAN MOTIVASI SIGNALIG DAN OPORTUNISTIK. - DEDI PUTRA; VINDA APRIANA (Universitas Bandar Lampung (UBL), 2018)
This study was aimed at testing the earning management and accounting information relevance : Signaling motivation and opportunistic approach. This research was conducted in Propoerty and Real Eastate Industues listed in The Indoneisa Stock Exchaange in the period of 2011-2014. The Sampling technique used was pusposive sampling method, with the criteria of property and real estate compenies consistently listed on the Stoxk Exchange in the year of 2011-2014 and actively engaged trade in stock. The result of this study indicated the value relevance of earning affected of the stock price, relevance of book value and cash flow did not influance the stock price. Earning management (short term discretionary accruals) did not affect the stock price while earnings managemen (long term discretionary accruals) and earning management (aggregate term discretionary accruals) affected on dtovk prices. Keyword: Earning Management, Relevance Of Accounting Informasi And Signaling Opportunistic.